Race and Sex Differences in Ambulatory Blood Pressure Measures among HIV+ Adults - Kent, Shia T. (J Am Soc Hypertens, 2017)
Ambulatory blood pressure monitoring (ABPM) can identify phenotypes that cannot be measured in the clinic. Determining race and sex disparities in ABPM measures among HIV+ individuals may improve strategies to diagnose and treat hypertension in this high risk population. We compared ABPM measures between 24 African American and 25 white HIV+ adults (36 men and 13 women). Awake systolic BP (SBP) and diastolic BP (DBP) were similar in African Americans and whites. After multivariable adjustment, sleep SBP and DBP were 9.7 (95%confidence interval [95%CI]: 4.7, 14.8) mmHg and 8.4 (95%CI: 4.3, 12.5) mmHg higher, respectively, among African Americans compared with whites. After multivariable adjustment, SBP and DBP dipping ratios were 5.2% (95%CI: 1.7%, 8.7%) and 6.1% (95%CI 2.0%, 10.3%) smaller among African Americans compared with whites. After multivariable adjustment, awake and sleep SBP and DBP were higher in men compared to women. There was no difference in SBP or DBP dipping ratios comparing men and women. The prevalence of awake masked hypertension was 42% in men versus 17% in women, and the prevalence of sleep masked hypertension was 57% among African Americans versus 18% among whites. These data suggest that ABPM measures differ by race and sex in HIV+ adults.